Requirement of the Mre11 Complex and Exonuclease 1 for Activation of the Mec1 Signaling Pathway - Nakada, Daisuke (American Society for Microbiology, 2004)
The large protein kinases, ataxia-telangiectasia mutated (ATM) and ATM-Rad3-related (ATR), orchestrate DNA damage checkpoint pathways. In budding yeast, ATM and ATR homologs are encoded by TEL1 and MEC1, respectively. The Mre11 complex consists of two highly related proteins, Mre11 and Rad50, and a third protein, Xrs2 in budding yeast or Nbs1 in mammals. The Mre11 complex controls the ATM/Tel1 signaling pathway in response to double-strand break (DSB) induction. We show here that the Mre11 complex functions together with exonuclease 1 (Exo1) in activation of the Mec1 signaling pathway after DNA damage and replication block. Mec1 controls the checkpoint responses following UV irradiation as well as DSB induction. Correspondingly, the Mre11 complex and Exo1 play an overlapping role in activation of DSB- and UV-induced checkpoints. The Mre11 complex and Exo1 collaborate in producing long single-stranded DNA (ssDNA) tails at DSB ends and promote Mec1 association with the DSBs. The Ddc1-Mec3-Rad17 complex associates with sites of DNA damage and modulates the Mec1 signaling pathway. However, Ddc1 association with DSBs does not require the function of the Mre11 complex and Exo1. Mec1 controls checkpoint responses to stalled DNA replication as well. Accordingly, the Mre11 complex and Exo1 contribute to activation of the replication checkpoint pathway. Our results provide a model in which the Mre11 complex and Exo1 cooperate in generating long ssDNA tracts and thereby facilitate Mec1 association with sites of DNA damage or replication block.